2007
DOI: 10.1038/sj.emboj.7601818
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β activates Erk MAP kinase signalling through direct phosphorylation of ShcA

Abstract: Erk1/Erk2 MAP kinases are key regulators of cell behaviour and their activation is generally associated with tyrosine kinase signalling. However, TGF-beta stimulation also activates Erk MAP kinases through an undefined mechanism, albeit to a much lower level than receptor tyrosine kinase stimulation. We report that upon TGF-beta stimulation, the activated TGF-beta type I receptor (TbetaRI) recruits and directly phosphorylates ShcA proteins on tyrosine and serine. This dual phosphorylation results from an intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
432
1
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(461 citation statements)
references
References 45 publications
17
432
1
11
Order By: Relevance
“…TGF-␤ receptors have been shown to possess dual tyrosine and serine kinase activity and can directly tyrosine phosphorylate ShcA to activate Ras/MAPK signaling or serine phosphorylate ShcA with an unclear consequence (10). The same study suggests that tyrosine phosphorylation of p66Shc, the inhibitory isoform of ShcA, is more dependent on RI in untransformed cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…TGF-␤ receptors have been shown to possess dual tyrosine and serine kinase activity and can directly tyrosine phosphorylate ShcA to activate Ras/MAPK signaling or serine phosphorylate ShcA with an unclear consequence (10). The same study suggests that tyrosine phosphorylation of p66Shc, the inhibitory isoform of ShcA, is more dependent on RI in untransformed cells.…”
Section: Discussionsupporting
confidence: 56%
“…The integration of TGF-␤-mediatedSmad-dependent and -independent signaling is believed to contribute to the key events of TGF-␤-induced tumor progression including ERK signaling-mediated cell migration (8,9). TGF-␤ activates Ras/ERK signaling through the direct phosphorylation of the adaptor protein ShcA (10). ShcA belongs to the family of Shc adaptor proteins, which are substrates of receptor tyrosine kinases (11).…”
mentioning
confidence: 99%
“…Thus, notwithstanding the involvement of TGF-β1 in CAVD, blocking those pathways may not be an option for treating CAVD and atherosclerosis. However, recent evidence has shown that TGF-β1 signalling pathways are much more complex and can involve tyrosine and serine/threonine phosphorylation and activation of MAP kinases , particularly ERK and p38 [56][57][58]. This investigation demonstrated a small but not statistically significant level of MAP kinase activity in VICs associated with TGFβ1-mediated Smad phosphorylation however this may reflect the 4 hour time point studied.…”
Section: We Investigated the Signaling Pathways Through Which Tgf-β1contrasting
confidence: 42%
“…Several mechanisms have been proposed for non-Smad TGF-␤ 1 signaling. For instance, T␤RI activates ERK by directly phosphorylating ShcA (27). PI3 kinase associates indirectly with T␤RI (66), and TGF-␤ 1 -induced Akt phosphorylation occurs independently of Smads in fibroblasts (60).…”
Section: Discussionmentioning
confidence: 99%